(untitled) (Al-Farooq Journal of Sciences, 2026)
The aim of this study is to investigate the isentropic efficiency of the high and intermediate pressure turbines in the third unit of the Al-Khoms steam power plant. Two samples of data have been used in this work. The first one was collected from the start-up data sheet of the power plant with a load of 120 MWH, and the second was collected from the current operation data sheet (June 2023) with a load of 96 MWH. The Engineering Equation Solver program (EES) has been used to represent h-S diagrams of the turbines in both samples of data and for the calculation. The results of the study show that the current isentropic efficiency of the high-pressure turbine is 41% and the intermediate-pressure turbine is 89%, while the commissioning start-up isentropic efficiency of the high-pressure turbine is 85% and the intermediate-pressure turbine is 98%, indicating that the isentropic efficiency of the turbines of the power plant decreased with time, especially in the high-pressure turbines, which decreased by 51%.